2003
DOI: 10.1016/s0885-3924(03)00334-8
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of reiki for the management of pain in advanced cancer patients

Abstract: This trial compared pain, quality of life, and analgesic use in a sample of patients with cancer pain (n=24) who received either standard opioid management plus rest (Arm A) or standard opioid management plus Reiki (Arm B). Participants either rested for 1.5 hr on Days 1 and 4 or received two Reiki treatments (Days 1 and 4) one hour after their first afternoon analgesic dose. Visual analogue scale (VAS) pain ratings, blood pressure, heart rate, and respirations were obtained before and after each treatment/res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
121
0
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(140 citation statements)
references
References 7 publications
7
121
0
9
Order By: Relevance
“…Moreover, the adverse effects of different drugs motivate the search for new approaches that might assist in the appropriate management of pain in this population, since this experience directly affects the quality of life, often leading to disability (10)(11) . Accordingly, non-pharmacological therapies such as acupuncture, light therapy with infrared monochrome laser therapy of low intensity, percutaneous electrical nerve transmission, reike, and electromagnetic stimulation (FREMS) have been used (12)(13)(14)(15)(16)(17)(18)(19) . However, there is no consensus on the use of these therapies, as effective remedy for the treatment of PDN.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the adverse effects of different drugs motivate the search for new approaches that might assist in the appropriate management of pain in this population, since this experience directly affects the quality of life, often leading to disability (10)(11) . Accordingly, non-pharmacological therapies such as acupuncture, light therapy with infrared monochrome laser therapy of low intensity, percutaneous electrical nerve transmission, reike, and electromagnetic stimulation (FREMS) have been used (12)(13)(14)(15)(16)(17)(18)(19) . However, there is no consensus on the use of these therapies, as effective remedy for the treatment of PDN.…”
Section: Introductionmentioning
confidence: 99%
“…This article shows the effects of reiki with symptom which the cancer patients suffered. Olson et al (2003) included twenty-five adults receiving palliative care for a pain rating greater than or equal to 3 on a 10-point VAS scale and requiring two to five breakthrough dosages of analgesia during the day were included in the study. Reiki treatment; participants also recorded use of analgesic medications in a daily diary.…”
Section: Reiki and Symptom Managementmentioning
confidence: 99%
“…A significant reduction in pain was reported on Days 1 and 4 by the opioid plus Reiki group and reported significant psychological improvement. Patients had been advised to continue their pain medications even if they felt better (Olson et al, 2003).…”
Section: Reiki and Symptom Managementmentioning
confidence: 99%
“…The uncontrolled studies found improvements in mixed chronic pain symptoms [38] and pain related to human immunodeficiency virus [39]. In the only controlled trial, Reiki showed modest evidence for shortterm reduction of cancer pain [40]. To summarize, little evidence from controlled trials currently supports the use of Reiki for pain.…”
Section: Reikimentioning
confidence: 99%